Anaesthesia care providers employed in humanitarian settings by Médecins Sans Frontières: a retrospective observational study of 173 084 surgical cases over 10 years. Issue 3 (4th March 2020) - Kudsk-Iversen, Søren; Trelles, Miguel; Ngowa Bakebaanitsa, Elie; Hagabimana, Longin; Momen, Abdul; Helmand, Rahmatullah; Saint Victor, Carline; Shah, Khalid; Masu, Adolphe; Kendell, Judith; Edgcombe, Hilary; English, Mike
Abstract : Objective: To describe the extent to which different categories of anaesthesia provider are used in humanitarian surgical projects and to explore the volume and nature of their surgical workload. Design: Descriptive analysis using 10 years (2008–2017) of routine case-level data linked with routine programme-level data from surgical projects run exclusively by Médecins Sans Frontières-Operational Centre Brussels (MSF-OCB). Setting: Projects were in contexts of natural disaster (ND, entire expatriate team deployed by MSF-OCB), active conflict (AC) and stable healthcare gaps (HG). In AC and HG settings, MSF-OCB support pre-existing local facilities. Hospital facilities ranged from basic health centres with surgical capabilities to tertiary referral centres. Participants: The full dataset included 178 814 surgical cases. These were categorised by most senior anaesthetic provider for the project, according to qualification: specialist physician anaesthesiologists, qualified nurse anaesthetists and uncertified anaesthesia providers. Primary outcome measure: Volume and nature of surgical workload of different anaesthesia providers. Results: Full routine data were available for 173 084 cases (96.8%): 2518 in ND, 42 225 in AC, 126 936 in HG. Anaesthesia was predominantly led by physician anaesthesiologists (100% in ND, 66% in AC and HG), then nurse anaesthetists (19% in AC and HG) or uncertified anaesthesia providers (15% in AC and HG). Across all settings and provider groups, patients were mostly healthy young adults (median age range 24–27 years), with predominantly females in HG contexts, and males in AC contexts. Overall intra-operative mortality was 0.2%. Conclusion: Our findings contribute to existing knowledge of the nature of anaesthetic provision in humanitarian settings, while demonstrating the value of high-quality, routine data collection at scale in this sector. Further evaluation of perioperative outcomes associated with different models of humanitarian anaesthetic provision is required.